Remoção de compostos orgânicos de água do Rio Uberabinha por filtração em carvão ativado reciclado - Boneberg, Daniela Garcia (2013)
Natural organic matter (NOM) is found in all surface, ground and soil waters. During recent decades, reports worldwide show a continuing increase in the color and NOM of the surface water, which has an adverse affect on drinking water purification. For several practical and hygienic reasons, the presence of NOM is undesirable in drinking water. Various technologies have been proposed for NOM removal with varying degrees of success. The properties and amount of NOM (natural organic matter) can hardly affect the process efficiency and it is known that raw water total organic carbon (TOC) levels have a potential to produce concentrations of trihalomethanes (THM). In order to improve and optimize these processes, the characterization and quantification of NOM at different purification and treatment processes stages is important. In this work, experimental measurements were conducted to reduce the level of natural organic matter for small amounts of Uberabinha River water. Treatment was tested for its efficacy to reduce raw water NOM using gravity filtration with recycled granular activated carbon. Four different particle sizes were used in the experiments. Samples of filtrate were collected in intervals of one hour and were analyzed for conductivity, pH and UV254 absorbance. The results showed that the system was able to reduce organic compounds. The use of recycled activated carbon showed a significant removal of total organic carbon (TOC). It was verified that pH and conductivity of the final product have not changed comparing to the raw water initial values. Also, the influence of pressure and the carbon particle size was clearly observed in the quantity and quality of the filtrate. The results indicated that the pressure variation influences the % removal of organic matter. The variation of time during the filtration did not impair the efficiency of each filter. In a nutshell, gravity filtration with recycled granular activated carbon was capable of reducing NOM to an acceptable level encouraging its recycling and use. With these results it seems that it could be appropriate as a device in the treatment of water in remote areas where water treated isn´t provided.